RISK MANAGEMENT FOR CONGREGATION-BASED FINANCING AT BMT NU CLURING BRANCH, BANYUWANGI - Arina Mana Sikana; Devi Kusana; Lely Ana Ferawati Ekaningsih (proceedings.icesy, 2026)
This study analyzes the implementation of the 5C principles (Character, Capacity, Capital, Collateral, Condition) in Islamic microfinance risk management. A case study was conducted at BMT NU Cluring Branch to understand the adaptive credit assessment mechanisms within the context of minimally collateralized financing. The research employed a descriptive qualitative method through in-depth interviews, field observations, and document studies. The findings indicate that Character is the dominant foundation, serving as effective "social collateral" through the gathering of soft information (Berger & Udell, 2002). Capacity and Capital analyses are conducted integratively with a contextual approach, while Collateral functions as a supportive mitigation tool. Proactive Condition analysis enables responsive financing adjustments. In conclusion, the 5C model at BMT NU represents a synthesis of modern credit frameworks, local wisdom, and substantive Islamic values, creating humane and sustainable risk management that strengthens partnership relations.